Analysis of Errors Solving Questions Final Semester Examination Mathematical Junior High School Students - Rizal, Muh; Paloloang, Baharuddin; Lefrida, Rita; Dahlia, Dahlia; Arivi, Maharani Agustina (Studies in Philosophy of Science and Education, 2024)
The aim of this study is to analyze the types of errors and the contributing factors in solving final semester mathematics exam questions among Grade VIII junior high school (JHS) students. This is a descriptive study using a qualitative approach. Data on errors were collected from the Final Semester Examination (FSE) results and through in-depth interviews with 28 Grade VIII JHS students in Palu City during the 2022/2023 academic year. Based on the analysis of five tested topics, number patterns, Cartesian coordinates, relations and functions, linear equations, and systems of linear equations in two variables, it was found that the most frequent errors were conceptual errors, particularly in the topics of Cartesian coordinates and linear equations. The main factors contributing to these errors include students’ inability to determine and apply appropriate formulas, as well as limited competency in performing calculation operations.